Optimasi Real-Time Sistem Pengendalian Informasi Berbasis IoT dan Barcode: Simulasi AnyLogic untuk Manajemen Pasar dan Sustainability - Theresya S Br Pardede, Valent; Fadillah, Dinda; Novira Sucipto , Tia; Febrina Soeharjo , Ira (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
This study designs a real-time simulation model using AnyLogic to evaluate the impact of IoT and barcode systems on inventory efficiency and sustainability in Indonesian retail (case study: Indomaret). Data were collected from 15 outlets in West Java over 12 months (2023), including IoT sensor readings (temperature, humidity) and 15,000 barcode transactions. Simulation results indicate IoT integration reduces stock loss by 40% and logistics carbon emissions by 18% via route optimization. The barcode system improves inventory accuracy to 98% and cuts stocktake time from 8 hours to 3 hours per outlet. These findings provide a technical framework for data-driven market management and support SDGs’ sustainability goals.